Intellectual Capital and Organizational Effectiveness: PLS-SEM approach - Zlatkovic, Мatea (Industrija, 2018)
An intellectual capital or intangible assets, as valuable economic resources, is increasingly becoming key driver of organizations' economic performance and competitiveness. The purpose of this research is to examine the three dimensions of intellectual capital i.e. human capital, structural capital, and relational capital, and their interdependence and, to test their direct and total effects on organizational effectiveness according to competing values approach. The proposed research model is tested in product-oriented and service-oriented organizations in the Republic of Srpska, Bosnia and Herzegovina, to establish similarities and differences within these two types of organizations. The research was performed using psychometrically validated questionnaires to measure intellectual capital and organizational effectiveness. To test hypothesized correlations partial least squares structural equation modelling (PLS-SEM) is employed. The main findings from this research are: interdependence of intellectual capital dimensions and their direct effects on certain organizational effectiveness models are significant in both types of organizations but in service-oriented organizations there is insignificant effect of human capital on structural capital, and, finally, total effects analysis shows that positive inter-dependence of intellectual capital dimensions increases the total positive effect of intellectual capital on organizational effectiveness. The final defined structural models show a robust explanation of the organizational effectiveness variance in observed context.
Keywords: Partial Least Squares Structural Equation Modeling; Relational Capital; Structural Capital; Human Capital; Competing Values Approach; Intellectual Capital; Organizational Effectiveness